POTENSI BAKTERI ASAM LAKTAT INDIGENOUS DALAM DEGRADASI ENZIMATIK ANTOSIANIN BERAS KETAN (Oryza sativa var. glutinosa) HITAM - , Nanik Suhartatik ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Some species of lactic acid bacteria show ô, D-glucosidase enzyme activity, enzyme groups that have an important role in the anthocyanin glycoside hydrolysis. Anthocyanin degradation metabolits were more stable, more beneficial to the body, and can be absorbed by the body better. In addition to fruits and vegetables, sources of anthocyanins noteworthy was black sticky rice, foods that more often consumed in fermented form, such as black glutinous rice tapai. The main aim of this research was to find the onformation about the potency of lactic acid bacteria producing enzyme ô glucosidase in the enzymatic degradation of black glutinous rice anthocyanins. The results showed that anthocyanins content of black glutinous rice are decreased after processed into tapai. Black glutinous rice anthocyanins characterization showed that the anthocyanins components in the black glutinous rice var. Setail was cyanidin-3- galactose, cyanidin-3- glucose, peonidin-3-galactose, peonidin-3-glucose, and peonidin-3-arabinose. Black glutinous rice var. Setail has antioxidant activity (% RSA DPPH) greater than the local black glutinous rice and white glutinous rice. Total phenolic content of black glutinous rice var. Setail reached 225.85 mg galat acid/100 mg and total anthocyanins equivalent to 145.17 mg/100 g sianidin-3- glucoside and reached 62.3 % RSA DPPH. There were 188 isolats that have a potential to be developed for further studies. From this step, 21 isolates were showed ô glucosidase activity. One isolate which was identified as as Pediococcus pentosaceus N11.16 where chosen to study the anthocyanin enzymatic degradation. Growth of selected bacteria in MRSm + Anthocyanins showed that the antioxidants activity was higher than MRS and MRSm. Radical Scavenging Activity of DPPH (%) was likely to be higher than the MRS in the early fermentation (0 s/d 8 h) and showed the same relative rate at the end of fermentation (8 s/d 20 h). FRAP values varied between treatments, MRSm showed higher ability to reduce Ferric ion, which is between 18.85 to 70.70%. While MRSm + Anthocyanins showed lower FRAP value, i.e between 2.00 to 36.75%. Beta glucosidase enzyme from P. pentosaceus N11.16 was an extracellular enzyme. Metabolites of enzymatic degradation of anthocyanins by P. pentosaceus N11.16 were gallic acid, protochatecuic acid, ô-coumaric acid, syringic acid, vanillic acid, homogentisic acid, and DMP propionic acid.